Catalyst Characterization with FESEM/EDX by the Example of Silver-Catalyzed Epoxidation of 1,3-Butadiene - Otto, Thomas N.; Habicht, Wilhelm; Dinjus, Eckhard; Zimmerman, Michael (IntechOpen, 2012)
None